POTENTIAL USE OF Pinus patula WOOD FOR THE PRODUCTION OF PURE AND IN COMBINATION WITH Eucalyptus PLYWOOD PANELS - Trianoski, Rosilani; Iwakiri, Setsuo; Matos, Jorge Luis Monteiro; Costa, Amanda Thaynara da Silva; Casagrande, Leandro Bertoli (Floresta, 2024)
Plywood panels are products of great importance in the global market, and Brazil is a large producer of conifer plywood, which boosts industrial activities in the south of the country and consequently contributes to the Brazilian GDP. Pinus patula is an unconventional species that requires study for this purpose. Thus, this research aimed to evaluate the potential for using Pinus patula wood for the production of pure plywood panels and in combination with Eucalyptus grandis and Eucalyptus dunnii. 8 treatments were produced, pure and in combination of species, which were glued with phenol formaldehyde adhesive, in a grammage of 180 g/m2 and a solids content from the adhesive formulation of 34%, and pressed at a temperature of 140°C for 13 minutes at a specific pressure of 11 kgf/cm2. Pinus taeda was used as a reference species. The physical and mechanical properties were evaluated according to the ABNT NBR 17002 and ABNT ISO 12466 standards. The results demonstrated that, for the majority of the properties evaluated, the Pinus patula panels were statistically equal or superior in relation to Pinus taeda. The “combi” type panels showed that the Eucalyptus species contributed to improving the static bending property. It is concluded, therefore, that Pinus patula has potential for the production of plywood panels, allowing an increase in the availability and diversity of raw materials for industrial processes, and that the static bending property can be improved with the production of panels of the “combi'' type using Eucalyptus veneers.